Determination of volatile aroma composition of some hazelnut varieties grown in Akçakoca conditions: Aroma diversity of hazelnut varieties - Unver, Hulya; Gucer, Yalcin; Haliscelik, Ozan; Sakar, Ebru; Sakar, Zeynep Mujde; Khanahmadi, Masoumeh; Ercisli, Sezai (Cellular and Molecular Biology, 2024)
Türkiye is leading country for hazelnut production and hazelnut orchards are widely established in Black Sea belt. Akçakoca district belongs to Duzce province is accepted as one of the most important production areas. In this research, volatile aroma components in nuts (kernels) of Çakıldak, Kara, Sarı (Mincane), Tombul and Yomra hazelnut varieties grown in Akçakoca district were determined by SPME/GC-MS. The analysis revealed the presence a total of 55 different volatile aroma components. These analyzes identified the presence of 39 descriptive volatile aroma compounds with significant differences between varieties. Çakıldak variety differed from the other varieties in terms of Isopentyl alcohol and Ethyl acetate components. At the same time, some volatile aroma compounds are commonly detected among the all varieties. This study has shown that the climate and soil conditions of Akçakoca cause the emergence of unique taste profiles through the effect of hazelnut varieties on volatile aroma components. The findings emphasize that regional diversity and local ecosystem factors play a critical role in determining flavor in hazelnut kernels. This study also emphasizes that variety selection is a critical factor in ensuring sustainability in hazelnut cultivation and that determining volatile aroma components is an important indicator in this selection.